Consumer Behaviour and Sustainable Fashion Consumption - Muthu, Subramanian Senthilkannan (Textile Science and Clothing Technology, 2019)
This book analyses the importance of consumer behaviour in sustainable fashion and consumption. Consumer behaviour plays a major role in sustainability, and when it comes to textile products, a number of studies have shown that for certain product categories, consumer behaviour during use and disposal stages influences the entire life cycle impacts of the product more than the raw material and manufacturing stages. However green the production, the overall sustainability of a product depends on the consumers who use and dispose of it.